Authentic leadership: A systematic review and research agenda - Polat, Eray; Arıcı, Hasan Evrim; Arasli, Hüseyin (Ege Akademik Bakis (Ege Academic Review), 2024)
The aim of this study is multifaceted. First, we focus on providing a comprehensive overview of research on authentic leadership (AL), which has attracted substantial research interest in the last few years. Second, we outline the theoretical and nomological network of AL, highlighting antecedents, outcomes, moderators, and mediators. Third, we offer an elaborated future research agenda to enable advances in theory and empirics. We systematically reviewed 182 articles issued in the business management and psychology literature between 2005 and 2021. Interest in AL is growing, and 2020 is the golden year. Developed countries dominate the field. After a rigorous review, we offer a future research agenda with four key themes. The study highlights that AL is critical to the emergence and growth of valuable behaviours, attitudes and performance at individual, team and organisational levels. The study provides new research ideas and further conceptualization of AL. We also provide a comprehensive review of why managers should continue to practice AL, where the literature has been, and where it may be headed in the future.
Keywords: Authentic leadership; leadership; authenticity; systematic literature review; İşletme; Business Administration